SIMULTANEOUS TRANSLATION AND ITS HISTORY - Toktasinov Dilshodbek; Axmedova Muhayyo (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Simultaneous translation is an essential tool that has become a prominent feature in the modern world. The translation method has revolutionized the way communication takes place in international forums and conferences. Its history dates back to the early 20th century when the world needed a way to promote international dialogue among nations. This article aims to explore the history of simultaneous translation and how it has impacted the world's communication.